Religion, law and dispute resolution in Canada and the USA: case studies of Islam and Judaism - Ghosn, Natalie Ann (Palgrave Macmillan, 2024)
The book is about the role of religious leadership in settling disputes of a legal nature within religious communities and the effects of this process on immigrant integration in Canada and the USA. The community-based practice of law in Jewish (Orthodox, Conservative and Reform) & Muslim (Sunni) communities in Canada and the USA are the communities studied here. The role of religious leadership, the gender implications of this type of dispute resolution and the implications for immigrant integration are all explored among a number of other topics. Natalie A. Ghosn, Esq. holds a Ph.D. in International Studies, as well as a B.A.,J.D./LLB. And LL.M. in International Law from the University of Miami. She has been an attorney with the Florida Bar since 2010, specializing in international criminal law and an academic in Nova Scotia at Acadia University teaching in the fields of law, justice and politics.